2014
DOI: 10.1007/s00402-014-2055-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of menarcheal age on the anterior cruciate ligament injury risk factors during single-legged drop landing in female artistic elite gymnasts

Abstract: The post-menarche group showed an increased noncontact anterior cruciate ligament injury risk, due to their greater knee loads, compared with the pre-menarche group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 50 publications
0
15
0
2
Order By: Relevance
“…All of these alterations to the body increase the loads experienced by the lower limb, including at the knee. In addition, the tendency for quadriceps dominance in girls develops during puberty [67,68], and extensive research has demonstrated a significant reduction in neuromuscular control of the knee in postpubescent vs prepubescent girls [13,32‐34,44,68,69]. Therefore, it seems that having a wider base of support in a child's body may not be especially risky, but keeping a wide base of support in an adolescent or young adult female's body may increase the risk of knee injury.…”
Section: Discussionmentioning
confidence: 99%
“…All of these alterations to the body increase the loads experienced by the lower limb, including at the knee. In addition, the tendency for quadriceps dominance in girls develops during puberty [67,68], and extensive research has demonstrated a significant reduction in neuromuscular control of the knee in postpubescent vs prepubescent girls [13,32‐34,44,68,69]. Therefore, it seems that having a wider base of support in a child's body may not be especially risky, but keeping a wide base of support in an adolescent or young adult female's body may increase the risk of knee injury.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,10 Divergent pubertal developmental trajectories in males and females likely underlie a suite of high-risk traits that appear widely in post-pubertal females, but less commonly in males. [11][12][13][14][15][16][17][18][19][20] Despite these broad sex-based distinctions, the process of puberty in terms of rates and timing of growth events is highly variable within each sex. Variation in pubertal development may therefore have effects on variability in ACL injury risk factors within females.…”
Section: Introductionmentioning
confidence: 99%
“…19,30 A substantial body of literature has shown that postpubertal females exhibit a tendency toward more valgus knee angles and loading than do males during the DVJ. 10,16,21,23,27,63 Greater valgus angulation and loading among females generate high frontal plane shear stress on the ACL, 26 making "valgus collapse" the most common mode of female injuries. 48 There also appears to be a relationship between the timing of pubertal development and the emergence of biomechanical risk factors in females.…”
mentioning
confidence: 99%